De arraial a patrimônio mundial: a redescoberta da Cidade de Goiás - Drogomirecki, Stephanie Botovchenco Rivera (2019)
Seeking to implement the powers to them entrusted by the Portuguese crown, and to organize the occupation in the Brazilians countryside, bandeirantes such as Bartolomeu Bueno da Silva and miners, like Manoel Rodrigues Tomar, founded in the captaincy of Goiás some “arraiais”, a kind of settlement without legal or administrative autonomy, which answered to their local villages (in this case, São Paulo). In this captaincy, one “arraial” stood out, both economically and politically: the Arraial de Sant'Ana, which became later known as Vila Boa. For centuries, this urban nucleus was essential to the state of Goiás economy and history. When the captaincy of Goiás started to feel the great impact of the region ́s gold shortage, many towns and cities were abandoned by the miners and eventually disappeared. However, Vila Boa (now known as Goiás) had survived this shortage, despite it also suffering a political impact in the early twentieth century when the capital was transferred to the modern city of Goiânia. After the loss of the State seat, some residents of the City of Goiás, allied to public agencies such as the National Institute of Historic and Artistic Heritage (Iphan), pooled their efforts in order to make the city the most important cultural heritage site of the state. When one acknowledges the importance of this city, one also has to discuss its rediscovery by means of its heritage, now heavily explored by the local tourism boards, as well as the impacts that this rediscovery of architecture and urbanism - through actions from Iphan and part of the city's residents – brought, and still bring, to the cultural and social scene of the state of Goiás, besides the fact that the city was conferred the World Heritage Site status from Unesco in 2001.